Expected Competencies and Capabilities of Data Librarians in Research Data Management According to the Harvard Biomedical Data Life Cycle: A Scoping Review - Zohreh Ehteshami; Azam Shahbodaghi; Mohammad Javad Mansourzadeh (پیاورد سلامت)
Background and Aim: An efficient data librarian equipped with the necessary competencies and capabilities is one of the most crucial elements in managing research data. The aim of this study is to identify the expected competencies and capabilities for data librarians in research data management according Harvard Biomedical Data Life Cycle. Materials and Methods: This study is a scoping review, utilizing the Harvard Biomedical Data Lifecycle model to systematically present the findings. To retrieve relevant literature, a search strategy was employed using related keywords in databases such as Scopus, PubMed, Web of Science, Google scholar and other reputable domestic databases, over the past five years. The research population comprised original research articles published in Persian and English that addressed the expected skills and capabilities for data librarians in managing research data. Results: Out of 5064 documents found, 196 were selected for full-text review. After reviewing the full texts, 17 studies were included in the research. In total, 92 competencies and capabilities were identified across 23 processes within the 7 stages of the Harvard Biomedical Data Lifecycle: 16 in the first stage, 16 in the second stage, 7 in the third stage, 15 in the fourth and fifth stages, 12 in the sixth stage, 8 in the seventh stage, and 18 general competencies and capabilities. According to the findings, the most studies focused on the competencies and capabilities required for the second stage, “Collection and Creation,” while the fewest studies addressed the seventh stage, “Publish and Reuse.” No studies mentioned competencies and capabilities for the processes “Image Management” in the third stage and “Preprints and Publishing” in the seventh stage. Conclusion: The results of this study indicate that among the various stages of the data lifecycle, the “Collection and Creation” stage received the most attention. Additionally, data librarians should possess not only specialized and professional skills but also general competencies and capabilities. It is recommended that the findings of this research be considered for designing short-term and long-term educational programs to train data librarians for research data managenet.